Periodontal health awareness and self-perceived halitosis among various professional students of West Godavari District of Andhra Pradesh - Gautami S Penmetsa; Swati Singh; Praveen Gadde; Ramya G Teja; Uday R Bhaskar (Wolters Kluwer Medknow Publications, 2017)
Introduction: Oral health is an essential part of maintaining overall health, and poor oral health can have a profound effect on the quality of life. Among the various sections of the population present in the society, professional students include a large group of population and are believed to have a better awareness pertaining to oral health than the common population. Aim: This study aims to determine the periodontal health awareness levels along with the self-perception of halitosis among the medical, pharmacy, and engineering students in the West Godavari district of Andhra Pradesh. Materials and Methods: A descriptive cross-sectional survey was conducted in 1230 students from medical, engineering, and pharmacy professions. A self-administered 27-item structured questionnaire was used to assess periodontal health and knowledge pertaining to oral hygiene practices along with the assessment of self-perceived halitosis. Tests of the association between self-perceived halitosis and the risk factors were conducted using Chi-square test. Intergroup comparison was conducted by ANOVA and t-test. Results: Self-perceived malodor reported was 50%, 54%, and 60% by medical, pharmacy, and engineering students, respectively. The difference in the levels of overall periodontal health awareness was statistically significant among the different specialities with the highest score gained by medical students (4.1 ± 2.0), followed by the pharmacy (2.9 ± 1.6), and engineering (1.6 ± 1.3) students. Conclusions: Even though professional students do have an acceptable level of knowledge regarding oral health, the level of awareness pertaining to periodontal health in particular is lacking. Hence, there is a need to extend the horizon for oral healthcare to other professional students at an elementary level.